Mantle Structure and Flow Across the Continent‐Ocean Transition of the Eastern North American Margin: Anisotropic S‐Wave Tomography. (14th December 2021) - Brunsvik, Brennan R.; Eilon, Zachary C.; Lynner, Colton
Abstract: Little has been seismically imaged through the lithosphere and mantle at rifted margins across the continent‐ocean transition. A 2014–2015 community seismic experiment deployed broadband seismic instruments across the shoreline of the eastern North American rifted margin. Previous shear‐wave splitting along the margin shows several perplexing patterns of anisotropy, and by proxy, mantle flow. Neither margin parallel offshore fast azimuths nor null splitting on the continental coast obviously accord with absolute plate motion, paleo‐spreading, or rift‐induced anisotropy. Splitting measurements, however, offer no depth constraints on anisotropy. Additionally, mantle structure has not yet been imaged in detail across the continent‐ocean transition. We used teleseismic S, SKS, SKKS, and PKS splitting and differential travel times recorded on ocean‐bottom seismometers, regional seismic networks, and EarthScope Transportable Array stations to conduct joint isotropic/anisotropic tomography across the margin. The velocity model reveals a transition from fast, thick, continental keel to low velocity, thinned lithosphere eastward. Imaged short wavelength velocity anomalies can be largely explained by edge‐driven convection or shear‐driven upwelling. We also find that layered anisotropy is prevalent across the margin. The anisotropic fast polarization is parallel to the margin within the asthenosphere. This suggests margin parallel flow beneath the plate. The lower oceanic lithosphere preserves paleo‐spreading‐parallel anisotropy, while the continental lithosphere has complex anisotropy reflecting several Wilson cycles. These results demonstrate the complex and active nature of a margin which is traditionally considered tectonically inactive. Plain Language Summary: North America was once connected to Africa, but the continents rifted apart and are now separated by the Atlantic Ocean. The nature of rifting on land has been thoroughly studied. However, it is much more difficult to study the offshore region where the thinned continent pinches out and the tectonic plate transitions to sea‐floor produced after continental breakup. Using a new data set from ocean‐bottom seismic stations, we construct a 3‐D image of seismic wavespeeds, which are diagnostic of rock type and temperature. We also image seismic anisotropy, which is the directional dependence of seismic velocity. Anisotropy is often used as a proxy for the orientation of stretching or mantle flow. We find wavespeed anomalies diagnostic of mantle upwelling associated with the shape and movement of the plate at the continent‐ocean transition. The anisotropy model suggests that, in this region, the mantle beneath the plates is currently flowing along the margin. Within the tectonic plates, the mantle preserves anisotropy developed during cycles of rifting and collision. These seismic wavespeed and anisotropy models demonstrate the complex and active nature of a continental margin that is traditionally considered tectonically inactive. Key Points: We conducted mantle‐scale velocity‐anisotropy tomography across the continent‐ocean transition of eastern North America The results capture layers of anisotropy preserved from collision and extension, as well as produced from modern mantle flow The imaged lithospheric and asthenospheric structure supports small‐scale convection and margin parallel asthenospheric flow